1973
DOI: 10.1063/1.1679027
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate interactions on a Pt(110) surface. I. Sulfur and carbon monoxide

Abstract: The kinetics of H2S adsorption on a Pt(110) crystal at T = 240°C were investigated by Auger electron spectroscopy. The sticking coefficient of H2S on a clean surface was constant up to θ = 0.6 and estimated near unity while for θ > 0.6 it decreased to about 0.03. A series of LEED patterns characteristic of adsorbed sulfur was observed with increasing sulfur coverage. The adsorption behavior of CO on clean and partially sulfurized Pt(110) surfaces was studied by flash desorption techniques. The resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(25 citation statements)
references
References 24 publications
6
18
0
1
Order By: Relevance
“…However, to the best of our knowledge, these two surfaces do not exhibit such a low temperature desorption peak [27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 97%
“…However, to the best of our knowledge, these two surfaces do not exhibit such a low temperature desorption peak [27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 97%
“…This assumption was tested using the simulation results. With respect to the collision theory, the pre‐exponential factor of a reaction between A and B is defined as: A=()rA+rB2()8πkBTμ0.5,where r A and r B are the molecular radius of reactants, which participated in collision. The calculated data by density functional theory have been used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…2(b) and Table l), indicating that either the residual poisoning effect of the SHion or the effect of dispersion pH may be the dominant factor (see later). Bonze1 and Ku (13) have shown that pre-adsorbed sulfur affects both the adsorption energy and the total amount of CO adsorbed on Pt(l11) surfaces. In the case of the Pd sol/SH-(0.01 mol dm-3) system, CO treatment of the flocculated sol did not result in sol redispersal and no v(CO),~, was observed in the infrared spectrum of the CO-treated flocculated palladium.…”
Section: Stability Of Hydrosol Towards Added Electrolytesmentioning
confidence: 99%